Challenges of Electronic Mobility in School Environments of Early Childhood Education - Sánchez-Blanco, Concepción (2021)
This essay reflects on the critical use of electronic media, the mobility of information they produce, and the educational challenges they pose to the early years of schooling. The paper puts emphasis on information and communication technologies (ICTs). It is based on results and conclusions from qualitative research the author conducted in this regard for several years (2012-2018) in Galicia (Spain). It is also based on the explanatory analysis of the role played by these media in society and the needs of children, teachers, and in general, school environments. School is immersed in a world where electronic mobility, driven by swiftness, breaks temporal and spatial boundaries. The search for simultaneity and the construction of planetary paths have made the information go in and out and be projected outside and inside the Earth. New realities and identities are emerging and can cause not a few difficulties but also find new ways and solutions to problems that were so far unsolvable. The ICTs use committed to justice and the fight against the exclusion should be part of the school interventions. From the earliest ages, children must have the opportunity to live in environments where such purposes are sought, and their experiences and ideas are heard. Electronic media should represent resources and not ends in themselves so that the ethical use of these is an essential condition for them to be truly educational resources. ICTs have given rise to complex realities in relation to which children of short ages build knowledge. They represent a source of teaching practices that must be analyzed in order to distance themselves from the exclusion and strive to seek equity, understanding the child’s point of view.